Pemahaman Konsep Operasi Hitung Bilangan Bulat Peserta Didik SMP melalui Brain-Based Learning - Raudhatul Jannah; Anizar Ahmad; M. Duskri (Universitas Syiah Kuala, 2019)
Curriculum 2013 mandates that learners should be able to understand mathematical concepts well, making it easier for learners to solve the problems of mathematics. However, there are still many students who are not able to understand mathematical concepts well, including the concept of integer arithmetic operations. This is because students think math as a complicated subject, so make the most of students do not like math. Therefore, teachers should be able to create learning that presents a fun and challenging atmosphere that make learners more excited. This study aims to determine the understanding of the concept of integer arithmetic operations of learners after participating in Brain-Based Learning. This type of research is experimental research with quantitative and qualitative approaches. This research was conducted in one of the Year 7 classes in the SMPIT Al-Azhar Banda Aceh. The results showed that the understanding of the concept of learners after participating in Brain-Based Learning (BBL) categorized as good, as seen from the values obtained by the four students were selected as subjects in this study. Learners who initially operate regardless of the sign of the times and to come to understand that multiplication and division should be done first. Likewise, with learners who initially was mistaken in operating the positive and negative integers, once implemented, BBL has been able to do it right and achieve some indicators of understanding of the concept.